Fluorine-doped long-circulation silicon-based negative electrode material and preparation method and application thereof
By doping fluoride in silicon-based materials to form a high-strength solid electrolyte interface, the problem of silicon-based materials' volume expansion, powderization and short cycle life in lithium-ion batteries is solved, and higher cycle stability and mass transfer rate are achieved.
Patent Information
- Application Number
- CN202411891545.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-20
AI Technical Summary
Silicon-based materials have problems such as large volume expansion rate, poor mass transfer ability, serious pulverization, many side reactions, poor rate performance and short cycle life in lithium-ion batteries, which limit their large-scale commercial applications.
By doping fluoride in silicon-based materials, F elements are used to form a LiF-rich high-strength solid electrolyte interface, which alleviates volume expansion and powdering, reduces the occurrence of side reactions, and improves the mass transfer rate.
It significantly improves the cycle stability of the silicon-based negative electrode material, extends the cycle life, and improves the mass transfer rate and conductivity of the material.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion battery electrode materials, and in particular relates to a silicon-based negative electrode material, a preparation method thereof, and a lithium-ion battery or lithium-ion secondary battery containing the same, and specifically relates to a fluorine-doped long-cycle silicon-based negative electrode material, a preparation method thereof, and an application thereof. Background Art
[0002] Lithium-ion batteries or lithium-ion secondary batteries have been widely used in various electronic products, electric vehicles and large-scale energy storage equipment due to their stable performance and mature technology. With the rapid development of related markets, they have been rapidly iterated, and negative issues such as safety and environmental pollution have been greatly reduced. Compared with traditional batteries, lithium-ion secondary batteries have the advantages of high energy density and good cycle performance. The market demand is still increasing and has become the mainstay of the energy storage field.
[0003] Lithium-ion secondary batteries are mainly provided with capacity by positive and negative electrode materials that can cyclically insert and remove lithium. The preparation of electrodes and the assembly process of batteries are also constantly optimized and improved with the development of science and technology. At the same time, based on the continuous replacement of various raw materials for lithium-ion batteries, developing new materials that are more suitable for market development needs is one of the current research directions.
[0004] Silicon-based materials have become one of the hot topics in the current research of negative electrode materials for lithium-ion secondary batteries due to their high specific capacity. The theoretical specific capacity of single silicon can reach 4200mAh / g, and the theoretical specific capacity of silicon oxide can also reach 2600mAh / g, which is much higher than the low theoretical specific capacity of 372mAh / g of commercial graphite negative electrode. Therefore, the development of commercial silicon-based negative electrode materials can meet the current market requirements for high specific energy batteries. However, although silicon-based materials have the advantage of high specific capacity, they also face defects such as severe pulverization, many side reactions, poor rate performance, and short cycle life caused by large volume expansion rate and poor mass transfer capacity. In addition, although the introduction of oxygen alleviates the volume expansion of silicon oxide, it deteriorates its conductivity and first-cycle coulomb efficiency.
[0005] Therefore, the above defects seriously restrict the large-scale commercial application of silicon-based materials. How to improve the cycle performance of silicon-based materials by alleviating problems such as large volume expansion rate and low mass transfer rate of silicon-based materials is the key and difficulty in promoting the industrial application of silicon-based negative electrode materials. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention proposes a fluorine-doped long-cycle silicon-based negative electrode material and a preparation method thereof. By using fluoride to dope and modify the silicon-based material, the doping of the F element can be used to continuously form a LiF-rich high-strength solid electrolyte interface (SEI) during the expansion and pulverization of silicon-based particles, thereby alleviating expansion and inhibiting pulverization, and reducing the occurrence of side reactions. At the same time, the F element doped into the interior can also improve the mass transfer rate, reduce the problems of uneven lithiation and stress concentration, and comprehensively improve the cycle stability of the silicon-based negative electrode.
[0007] Furthermore, the present invention also provides the use of the fluorine-doped long-cycle silicon-based negative electrode material in the preparation of lithium-ion batteries or lithium-ion secondary batteries.
[0008] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0009] A method for preparing a fluorine-doped long-cycle silicon-based negative electrode material comprises selecting a suitable fluorine-containing precursor and a silicon-based material, performing doping modification by grinding and annealing, thereby obtaining a fluorine-doped modified silicon-based negative electrode material.
[0010] The preparation method specifically comprises the following steps:
[0011] Step 1): mixing a certain amount of fluorine-containing precursor and a certain amount of silicon-based material, and then physically grinding and mixing to obtain a mixture I;
[0012] Step 2): Place the mixture I in a tube furnace, uniformly heat it to a certain temperature under an inert atmosphere and a certain pressure condition for high-temperature doping heat treatment, and then naturally cool it to room temperature (25±5°C) to obtain a fluorine-doped long-cycle silicon-based negative electrode material.
[0013] Furthermore, the silicon-based material in step 1) is pure silicon or silicon monoxide (SiO x ) powder material, wherein the median particle size D50 of pure silicon powder is 0.05-10 μm, silicon dioxide (SiO x ) The median particle size D50 of the powder is 0.5-20 μm, and the silicon dioxide (SiO x ) in which the atomic ratio of silicon and oxygen is (0.2-5):1, preferably (0.2-0.9):1; or, the silicon oxide SiO x The atomic proportion of silicon in the material is 61% to 64%.
[0014] Furthermore, the fluorine-containing precursor described in step 1) includes but is not limited to one or more of tin tetrafluoride, stannous fluoride, magnesium fluoride, aluminum fluoride, antimony fluoride, lanthanum fluoride, yttrium fluoride, iron fluoride, nickel fluoride, ammonium fluoride, ammonium fluoroborate, etc.
[0015] Furthermore, in step 1), the molar ratio of the silicon-based material to the fluorine-containing precursor is 200:1 to 1:20.
[0016] Furthermore, the equipment used for the physical grinding and mixing in step 1) is a high-speed ball mill mixing equipment, a horizontal ball mill, a stirring ball mill, a VC-type mixing equipment or a V-type mixing equipment, etc., the mixing time is 0.02 to 12 hours, and the rotation speed is 50 to 2000 rpm.
[0017] Furthermore, the high temperature doping heat treatment in step 2) is modified calcination.
[0018] Furthermore, during the high-temperature doping heat treatment in step 2), the inert atmosphere is formed by a mixed gas of one or more of nitrogen, argon, and helium; the gas flow rate under the inert atmosphere is 0.2 to 10 L / min, and the ventilation time is 0.2 to 20 h.
[0019] Furthermore, the high temperature doping heat treatment in step 2) is to keep the temperature at 200°C to 1000°C for 0.01 to 5 hours.
[0020] Furthermore, the heating rate during the high temperature doping heat treatment in step 2) is 1-10°C / min.
[0021] Further preferably, the procedure of the high temperature doping heat treatment in step 2) can also be: first keep the temperature at 200℃~600℃ for 0.01h~3h, then heat to 600℃~1000℃ and keep the temperature for 0.01h~5h, and the heating rate is 1~10℃ / min.
[0022] Further preferably, the pressure during the high temperature doping heat treatment in step 2) is (0.9 to 1.2) atmospheres, preferably normal pressure.
[0023] As another preferred technical solution, the method for preparing the fluorine-doped long-cycle silicon-based negative electrode material of the present application comprises the following steps:
[0024] Step (1): mixing a certain amount of fluorine-containing precursor and a certain amount of silicon-based material, and then physically grinding and mixing the materials to obtain a mixture II;
[0025] Step (2): Mixing the mixture II in step (1) with a certain amount of carbon-containing precursor and then physically grinding and mixing the mixture to obtain a mixture III;
[0026] Step (3): Place mixture III in a tube furnace, and in an inert atmosphere and under certain pressure conditions, uniformly heat it to a certain temperature for high-temperature doping heat treatment, and then naturally cool it to room temperature (25±5°C) to obtain a fluorine-doped long-cycle silicon-based negative electrode material.
[0027] Furthermore, the silicon-based material in step (1) is pure silicon or silicon dioxide (SiO x ) powder material, wherein the median particle size D50 of pure silicon powder is 0.05-10 μm, silicon dioxide (SiO x ) The median particle size D50 of the powder is 0.5-20 μm, and the silicon dioxide (SiO x ) in which the atomic ratio of silicon and oxygen is (0.2-5):1, preferably (0.2-0.9):1; or, the silicon oxide SiO x The atomic proportion of silicon in the material is 61% to 64%.
[0028] Furthermore, the fluorine-containing precursor described in step (1) includes but is not limited to one or more of tin tetrafluoride, stannous fluoride, magnesium fluoride, aluminum fluoride, antimony fluoride, lanthanum fluoride, yttrium fluoride, iron fluoride, nickel fluoride, ammonium fluoride, ammonium fluoroborate, etc.
[0029] Furthermore, in step (1), the molar ratio of the silicon-based material to the fluorine-containing precursor is 200:1 to 1:20.
[0030] Furthermore, the equipment used for the physical grinding and mixing in step (1) and step (2) is a high-speed ball mill mixing equipment, a horizontal ball mill, a stirring ball mill, a VC-type mixing equipment or a V-type mixing equipment, etc., the mixing time is 0.02 to 12 hours, and the rotation speed is 50 to 2000 rpm.
[0031] Furthermore, the carbon-containing precursor in step (2) includes but is not limited to one or more of asphalt (coal-based mesophase asphalt, coal tar asphalt, petroleum asphalt, etc.), biomass and its derivatives (cellulose, lignin, glucose, starch, chitosan, sucrose, humic acid, etc.), chemical materials (phenolic resin, urea, citric acid, etc.), etc.
[0032] Furthermore, in step (2), the mass ratio of the carbon-containing precursor to the silicon-based material is (0.01-5):1.
[0033] Furthermore, the high temperature doping heat treatment in step (3) is modified calcination.
[0034] Furthermore, during the high-temperature doping heat treatment in step (3), the inert atmosphere is formed by a mixed gas of one or more of nitrogen, argon, and helium; the gas flow rate under the inert atmosphere is 0.2 to 10 L / min, and the ventilation time is 0.2 to 20 h.
[0035] Furthermore, the high temperature doping heat treatment in step (3) is to keep the temperature at 200°C to 1000°C for 0.01 to 5 hours.
[0036] Furthermore, the heating rate during the high temperature doping heat treatment in step (3) is 1 to 10° C. / min.
[0037] Further preferably, the procedure of the high temperature doping heat treatment in step (3) can also be: first keep the temperature at 200℃~600℃ for 0.01h~3h, then heat to 600℃~1000℃ and keep the temperature for 0.01h~5h, with a heating rate of 1~10℃ / min.
[0038] Further preferably, the pressure during the high temperature doping heat treatment in step 2) is (0.9 to 1.2) atmospheres, preferably normal pressure.
[0039] Furthermore, the present invention also provides a fluorine-doped long-cycle silicon-based negative electrode material prepared by the above method, wherein the negative electrode material has a morphology similar to that of the silicon-based material precursor, and fluorine is uniformly doped inside the silicon-based particles. At the same time, other elements in some precursors may be doped in the silicon-based particles and loaded on the surface, forming a synergistic effect with the fluorine doping.
[0040] Furthermore, based on a general inventive concept, the present invention also provides the use of the fluorine-doped long-cycle silicon-based negative electrode material in the preparation of lithium-ion batteries or lithium-ion secondary batteries.
[0041] Further, based on a general inventive concept, the present invention also provides a method for preparing a lithium ion battery or a lithium ion secondary battery using the fluorine-doped long-cycle silicon-based negative electrode material, comprising the following steps:
[0042] a) Preparation of mixed powder: placing a certain amount of active material, binder, conductive agent and single-walled carbon nanotubes in a container to obtain mixed powder;
[0043] b) Preparation of mixed slurry: Then add solvent to the mixed powder in step a), ultrasonically disperse at a power of 80 to 100 W for 8 to 12 minutes, put a polytetrafluoroethylene magnet in a container and stir at a speed of 300 to 400 r / min for 8 to 12 hours to evenly disperse the fluorine-doped long-cycle silicon-based negative electrode material, binder, conductive agent and single-walled carbon nanotubes to obtain a mixed slurry;
[0044] c) Button cell assembly: the mixed slurry in step b) is coated on a copper foil (current collector), dried at 60-80° C. for 8-12 h, and then made into a button-type electrode disc with a diameter of 12 mm; then, the prepared electrode disc is used as a working electrode, the metal lithium sheet is used as a counter electrode, and the prepared electrode disc, metal lithium sheet, diaphragm, and electrolyte are assembled into a button cell, and the battery model is a CR2032 button cell.
[0045] Specifically, the active material in step a) is a fluorine-doped silicon-based negative electrode material, or a composite negative electrode material formed by a fluorine-doped silicon-based material and graphite, wherein the mass ratio of the fluorine-doped silicon-based material to the graphite in the fluorine-doped silicon-based material / graphite composite negative electrode material is 1:(1-10).
[0046] Specifically, in step a), the conductive agent is carbon black (Super-P) or acetylene black.
[0047] The binder in step a) is one or more of carboxymethyl cellulose, sodium alginate, ammonium alginate, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylic acid (PPA), lithiated polyacrylic acid (lithiated PPA), styrene-butadiene rubber and polystyrene-butadiene copolymer.
[0048] Further preferably, the binder is a mixture of carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR), the mass ratio of the two being 1:(1-2), preferably 1:1.
[0049] Specifically, the solvent is selected from one of deionized water, ethanol and NMP.
[0050] Specifically, the mass of the solvent is 2 to 12 times the mass of the mixed powder.
[0051] Specifically, in the mixed slurry obtained in step b), the weight ratio of the active material, the conductive agent, the binder, and the single-walled carbon nanotube is (80-95): (1-10): (3-10): (0.2-2).
[0052] Specifically, in step b), the loading amount of the mixed slurry on the prepared electrode disc is 1 to 10 mg / cm 2 .
[0053] Specifically, in step c), the diaphragm type is a polypropylene diaphragm Celgard2400, and the main component of the electrolyte used in the battery is: lithium salt (lithium hexafluorophosphate); preferably, the electrolyte is 1M LiPF added with 5% fluoroethylene carbonate FEC 6 / EC+DMC(V / V=1:1).
[0054] Furthermore, based on a general inventive concept, the present invention also provides a lithium ion battery or a lithium ion secondary battery prepared by the above method.
[0055] Compared with the prior art, the advantages of the present invention are:
[0056] 1. The present invention provides a method for preparing a fluorine-doped long-cycle silicon-based negative electrode material which is simple to operate, has cheap raw materials and is easy to mass produce. It has the advantages of high commercial value and is easy to mass produce.
[0057] 2. The silicon-based composite negative electrode material prepared by the method of the present invention significantly exhibits fluorine doping characteristics, and can form a self-healing high-strength solid electrolyte interface during the cycle process, ensuring excellent cycle stability; the partially fluorinated precursor also exhibits dual-element doping characteristics, combining solid phase doping with surface nanocluster loading, effectively improving the mass transfer rate of the material and reducing stress concentration, thereby significantly extending the cycle life of the material, which makes it show broad application prospects in the field of lithium-ion battery negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 The fluorine-doped long-cycle SiO prepared in Example 1 x SEM structure of the composite negative electrode material;
[0059] Figure 2 The cycle performance diagram of Examples 1 to 2 of the present invention and Comparative Examples 1 to 2 at 1 A / g;
[0060] Figure 3 It is a cycle performance diagram of Example 3 of the present invention and Comparative Example 3 at 1 A / g. DETAILED DESCRIPTION
[0061] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0062] Unless otherwise specified, the experimental methods used in the following examples and comparative examples are all conventional methods; the reagents, raw materials, etc. used in the following examples, unless otherwise specified, are all conventional commercially available products and can be obtained from commercial channels.
[0063] The micron-sized Si and micron-sized silicon dioxide SiO used in the following examples and comparative examples are: x All of them are in powder form and are produced by Shanghai Xiangtian Nanomaterials Co., Ltd. The product number of micron-sized Si is XT-SI-06, and its median particle size D50 is 5 μm; micron-sized SiO x The product number is XT-SIO-5U, the median particle size D50 is 5μm, and the silicon-oxygen atomic ratio is 6:4.
[0064] Stannous fluoride powder (article number T195033-100 g) was purchased from Aladdin Biochemical Technology Co., Ltd. The purity of the argon gas used in the following examples and comparative examples was 99.99%.
[0065] Example 1
[0066] Example 1 provides a method for preparing a fluorine-doped long-cycle silicon-based negative electrode material, the specific steps of which are:
[0067] Step 1: Micron-sized silicon dioxide SiO x The powder was mixed with stannous fluoride powder at a molar ratio of 100:1, and ground and mixed using a MSK-PCV-300 planetary vacuum centrifugal mixer produced by Kejing Company at a grinding speed of 800 rpm for half an hour to obtain a mixture A;
[0068] Step 2: Place mixture A in a tube furnace, exclude air, introduce high-purity argon gas at a flow rate of 0.8 L / min, and heat at a rate of 5 °C / min in an argon atmosphere at normal pressure. After heating to 600 °C, keep the temperature for 2 h for calcination and doping at normal pressure, and then cool naturally to room temperature (25 ± 5 °C) to obtain fluorine-doped long-cycle SiO x Base negative electrode material I.
[0069] Example 2
[0070] Example 2 provides a method for preparing a fluorine-doped long-cycle silicon-based negative electrode material, the specific steps of which are:
[0071] Step 1: Mix the mixture A in Example 1 with coal-based mesophase pitch (Shandong Keneng New Carbon Material Technology Co., Ltd., ash content <350ppm, coking value ≥90%, mesophase content ≥95%), the mass ratio of mixture A to coal-based mesophase pitch is 8:2, and the MSK-SFM-14-IVS rolling ball mill of Kejing Company is used for ball milling mixing, the ball milling speed is 300rmp, and the ball milling mixing time is 10h to obtain a mixture B;
[0072] Step 2: Mixture B was placed in a tube furnace, air was removed, high-purity argon was introduced, and the argon flow rate was 0.8 L / min. In a normal pressure argon atmosphere, the temperature was raised at a rate of 5 ° C / min, and then heated to 310 ° C and kept for 2 hours to soften the asphalt. Then, the temperature was continued to be raised to 900 ° C at a rate of 5 ° C / min and kept for 2 hours for carbonization coating, and then naturally cooled to room temperature (25 ± 5 ° C) to obtain a modified fluorine-doped long-cycle SiO x Base negative electrode material II.
[0073] Example 3
[0074] Example 3 provides a method for preparing a fluorine-doped long-cycle silicon-based negative electrode material, the specific steps of which are:
[0075] Step 1: Mix the micron-sized silicon powder and the stannous fluoride powder in a molar ratio of 50:1, and grind and mix them using a MSK-PCV-300 planetary vacuum centrifugal mixer produced by Kejing Company at a grinding speed of 800 rpm for half an hour to obtain a mixture C;
[0076] Step 2: Place mixture C into a tubular furnace, exclude air, introduce high-purity argon gas at a flow rate of 0.8 L / min, and heat it at a rate of 5°C / min in a normal pressure argon atmosphere. After heating to 900°C, keep it warm for 2 hours for normal pressure calcination and doping, and then naturally cool it to room temperature (25±5°C) to obtain a modified fluorine-doped long-cycle Si-based negative electrode material III.
[0077] The morphology and particle size of the product of Example 1 were observed using a scanning electron microscope. The SEM image obtained is as follows: Figure 1 As shown in the figure, micron-sized silicon dioxide particles and a small amount of debris can be seen in the sample, and the surface is intact.
[0078] Comparative Example 1
[0079] The original micron-sized silicon dioxide SiO x The powder is directly used as negative electrode material.
[0080] Comparative Example 2
[0081] The original micron-sized silicon dioxide SiO x The powder was placed in a tube furnace, the air was removed, and high-purity argon was introduced at a flow rate of 0.8 L / min. The temperature was raised at a rate of 5 °C / min in an argon atmosphere at normal pressure. After reaching 600 °C, the temperature was kept for 2 h for normal pressure calcination, and then the temperature was naturally lowered to room temperature (25 ± 5 °C) to obtain heat-treated SiO x Material IV.
[0082] Comparative Example 3
[0083] The original micron-sized silicon powder without any treatment is directly used as the negative electrode material.
[0084] Performance Testing
[0085] The products prepared in Examples 1-3 and Comparative Examples 1-3 were assembled into batteries and subjected to electrochemical performance tests (the test method refers to Wang, Haolin, et al. "What Is the Real Origin of Single-Walled Carbon Nanotubes for the Performance Enhancement of Si-Based Anodes?" Journal of the American Chemical Society 2024, 146 (25), 17041-17053). The specific method is as follows:
[0086] a) Preparation of mixed powder: Active material (the product prepared in Examples 1, 2, 3 or Comparative Examples 1, 2, 3), binder CMC:SBR (the mass ratio of CMC to SBR is 1:1, CMC model MAC500LC, SBR model JSR TRD104A, both purchased from Shenzhen Kejing Zhida Technology Co., Ltd.), carbon black Super P (carbon-based conductive agent, purchased from Shenzhen Kejing Zhida Technology Co., Ltd., brand CAS1333-86-4), and single-walled carbon nanotubes (purchased from Dongguan Kelude New Energy Technology Co., Ltd., product number MA-EN-CO-0010) are mixed in a mass ratio of 90:5:4:1 to obtain a mixed powder;
[0087] b) Preparation of mixed slurry: then add the mixed powder in step a) into a solvent (deionized water), place in a mixing container and mix evenly, the mass of the solvent is 2.5 times the mass of the mixed powder, then put a polytetrafluoroethylene magnet in the mixing container and stir at a speed of 400r / min for 10h to make the active substance, binder CMC+SBR, carbon black Super-P, and single-walled carbon nanotubes disperse evenly to obtain a mixed slurry;
[0088] c) Button cell assembly and performance testing: The mixed slurry in step b) was coated on copper foil (current collector) and vacuum dried at 80°C for 12 h to prepare a battery with a loading of 1.5 mg / cm 2 The negative electrode sheet is then cut into a button-type electrode disc with a diameter of 12 mm using a slicer;
[0089] The CR2032 button cell model was used, with a metal lithium sheet as the counter electrode, a Celgard 2400 diaphragm, and an electrolyte (Suzhou Duoduo Chemical Technology Co., Ltd., item number LB-007) of 1 M LiPF with 5% fluoroethylene carbonate FEC added. 6 / EC+DMC (V / V=1:1), the prepared negative electrode disc, metal lithium sheet (as counter electrode), separator and electrolyte are assembled into a button battery.
[0090] The cycle performance test was carried out under the following conditions: the electrode was activated by cycling for 3 cycles at a current density of 0.1 A / g, and then a constant current charge and discharge cycle test was carried out at a high current density of 1 A / g, with a charge and discharge voltage range of 0.01 to 2 V.
[0091] According to the above-mentioned battery assembly and testing method, the cycle performance of the fluorine-doped long-cycle silicon-based negative electrode materials prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3 was tested according to the above-mentioned battery assembly and testing method, and the performance comparison diagram was obtained as shown in FIG. Figure 2 , 3 shown.
[0092] from Figure 2 , 3 It can be seen that the fluorine-doped long-cycle SiO x The first efficiency of the base negative electrode material I is 80%, and the capacity retention rate after 300 cycles at 1A / g is 83.8% (1126.3 mAh / g); the fluorine-doped long-cycle SiO x The first efficiency of the base negative electrode material II is 84%, and the capacity retention rate after 300 cycles at 1A / g is 90.4% (1130mAh / g), while the comparative example shows a significant performance degradation. Figure 3 In the performance comparison of the fluorine-doped long-cycle Si-based negative electrode material III (Example 3) and the original micron silicon (Comparative Example 3), it can be seen that Example 3 also shows a relatively slow performance decline, and the capacity retention rate after 100 cycles is 43.4%, which is much higher than the 20.5% of Comparative Sample 3. The above data show that the use of fluorine-containing precursors to dope and modify silicon-based negative electrodes such as silicon, sub-silicon and silicon carbon can effectively improve their cycle performance.
[0093] In summary, the present invention uses fluorine-doping to modify silicon-based materials through fluorine-containing precursors, and can utilize the doping of fluorine elements to continuously form a LiF-rich high-strength solid electrolyte interface (SEI) during the expansion and pulverization of silicon-based particles, thereby alleviating expansion and inhibiting pulverization, and reducing the occurrence of side reactions. At the same time, fluorine and other elements doped into the silicon-based materials can further improve the mass transfer rate of the silicon-based material bulk phase, reduce the problems of uneven lithiation and stress concentration, and comprehensively improve the cycle stability of the silicon-based negative electrode.
[0094] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a fluorine-doped long-cycle silicon-based negative electrode material, characterized in that: The following steps are involved: Step 1): a certain amount of fluorine-containing precursor and a certain amount of silicon-based material are mixed and then physically ground and mixed to obtain a mixture I; Step 2): The mixture I is heated to a certain temperature under an inert atmosphere and a certain pressure condition for high-temperature doping heat treatment, and then naturally cooled to room temperature to obtain a fluorine-doped long-cycle silicon-based negative electrode material.
2. The preparation method according to claim 1, characterized in that In step 1), the silicon-based material is a powder material of pure silicon or silicon oxide, wherein the median particle size D50 of the pure silicon powder is 0.05-10 μm, the median particle size D50 of the silicon oxide powder is 0.5-20 μm, and the atomic ratio of silicon to oxygen in silicon oxide is (0.2-5):1; or, the atomic ratio of silicon in silicon oxide is 61%~64%; The fluorine-containing precursor in step 1) is one or more of tin tetrafluoride, stannous fluoride, magnesium fluoride, aluminum fluoride, antimony fluoride, lanthanum fluoride, yttrium fluoride, iron fluoride, nickel fluoride, ammonium fluoride, and ammonium fluoroborate; Step 1) The molar ratio of the silicon-based material to the fluorine-containing precursor is 200:1 to 1:
20.
3. The preparation method according to claim 1, characterized in that: During the high-temperature doping heat treatment in step 2), the inert atmosphere is formed by a mixed gas of one or more of nitrogen, argon, and helium; the gas flow rate under the inert atmosphere is 0.2 to 10 L / min, and the ventilation time is 0.2 to 20 h; The high temperature doping heat treatment in step 2) is to keep the temperature at 200°C to 1000°C for 0.01 to 5 hours.
4. A method for preparing a fluorine-doped long-cycle silicon-based negative electrode material, characterized in that: The following steps are involved: Step (1): mixing a certain amount of fluorine-containing precursor and a certain amount of silicon-based material, and then physically grinding and mixing the mixture to obtain a mixture II; Step (2): Mixing the mixture II in step (1) with a certain amount of carbon-containing precursor and then physically grinding and mixing the mixture to obtain a mixture III; Step (3): The mixture III is heated to a certain temperature under an inert atmosphere and a certain pressure to perform a high-temperature doping heat treatment, and then naturally cooled to room temperature to obtain a fluorine-doped long-cycle silicon-based negative electrode material.
5. The preparation method according to claim 4, characterized in that: The silicon-based material in step (1) is a powder material of pure silicon or silicon monoxide, wherein the median particle size D50 of the pure silicon powder is 0.05-10 μm, the median particle size D50 of the silicon monoxide powder is 0.5-20 μm, and the atomic ratio of silicon to oxygen in silicon monoxide is (0.2-5):1; or, the atomic ratio of silicon in silicon monoxide is 61%~64%; The fluorine-containing precursor in step (1) is one or more of tin tetrafluoride, stannous fluoride, magnesium fluoride, aluminum fluoride, antimony fluoride, lanthanum fluoride, yttrium fluoride, iron fluoride, nickel fluoride, ammonium fluoride, and ammonium fluoroborate; In step (1), the molar ratio of the silicon-based material to the fluorine-containing precursor is 200:1 to 1:
20.
6. The preparation method according to claim 4, characterized in that: The carbon-containing precursor in step (2) is one or more of asphalt, biomass and its derivatives, and chemical materials; The mass ratio of the carbon-containing precursor to the silicon-based material in step (2) is (0.01-5):
1.
7. The preparation method according to claim 4, characterized in that: During the high-temperature doping heat treatment in step (3), the inert atmosphere is formed by a mixed gas of one or more of nitrogen, argon, and helium; the gas flow rate under the inert atmosphere is 0.2 to 10 L / min, and the ventilation time is 0.2 to 20 h.
8. The preparation method according to claim 4, characterized in that: The high temperature doping heat treatment in step (3) is to keep the temperature at 200°C to 1000°C for 0.01 to 5 hours.
9. A fluorine-doped long-cycle silicon-based negative electrode material prepared by the method according to any one of claims 1 to 8.
10. Use of the fluorine-doped long-cycle silicon-based negative electrode material according to claim 9 in the preparation of lithium-ion batteries or lithium-ion secondary batteries.
Citation Information
Patent Citations
Fluorine-containing silicon monoxide negative electrode material and preparation method and application thereof
CN110890540A
Preparation method and application of fluorine-containing silicon tin composite negative electrode material
CN117154065A
High-performance resin-based hard carbon negative electrode material and preparation method and application thereof
CN117682503A
Coated silicon negative electrode material and preparation method and application thereof
CN117976832A
Lithium fluoride bulk phase doped silicon material and preparation method and application thereof
CN118198363A
Cited By
Silicon-based negative electrode material and preparation method and application thereof
CN120097346A
Silicon-based self-supporting electrode material and preparation method and application thereof
CN121905825A